Individual or mixing extrusion of Tartary buckwheat and adzuki bean: Effect on quality properties and starch digestibility of instant powder - Zhang, Zhuo; Liang, Yongqiang; Zou, Liang; Xu, Yunan; Li, Mengzhuo; Xing, Bao; Zhu, Manli; Hu, Yichen; Ren, Guixing; Zhang, Lizhen; Qin, Peiyou (Frontiers in Nutrition, 2023)
Introduction Tartary buckwheat and adzuki bean, which are classified as coarse grain, has attracted increasing attention as potential functional ingredient or food source because of their high levels of bioactive components and various health benefits. Methods This work investigated the effect of two different extrusion modes including individual extrusion and mixing extrusion on the phytochemical compositions, physicochemical properties and in vitro starch digestibility of instant powder which consists mainly of Tartary buckwheat and adzuki bean flour. Results Compared to mixing extrusion, instant powder obtained with individual extrusion retained higher levels of protein, resistant starch, polyphenols, flavonoids and lower gelatinization degree and estimated glycemic index. The α-glucosidase inhibitory activity (35.45%) of the instant powder obtained with individual extrusion was stronger than that obtained with mixing extrusion (26.58%). Lower levels of digestibility (39.65%) and slower digestion rate coefficient (0.25 min−1) were observed in the instant powder obtained with individual extrusion than in mixing extrusion (50.40%, 0.40 min−1) by logarithm-of-slope analysis. Moreover, two extrusion modes had no significant impact on the sensory quality of instant powder. Correlation analysis showed that the flavonoids were significantly correlated with physicochemical properties and starch digestibility of the instant powder. Discussion These findings suggest that the instant powder obtained with individual extrusion could be used as an ideal functional food resource with anti-diabetic potential.